Rapid and Acute Effects of Estrogen on Time Perception in Male and Female Rats - Pleil, Kristen; Cordes, Sara; Meck, Warren H.; Williams, Christina L. (Frontiers in Integrative Neuroscience, 2011)
Sex differences in the rapid and acute effects of estrodiol on time perception were investigated in adult male and female Sprague-Dawley rats. Because estrodiol has been shown to increase striatal dopamine release, it may be able to modify time perception and timed performance by increasing the speed of an internal clock in a manner similar to indirect dopamine agonists such as amphetamine and cocaine. Two groups of females (neonatally estradiol-treated/adult ovariectomized and neonatally oil-treated/adult ovariectomized) and 2 groups of males (neonatally castrated and adult castrated) were trained in a 2 s vs. 8 s duration bisection procedure and tested using intermediate signal durations. After obtaining oil-injected baseline psychometric functions over several days, rats were administered 5μg of estradiol for 4 days and behaviorally evaluated 30 min following each injection. This oil-estradiol administration cycle was subsequently repeated 3 times following the re-establishment of baseline training. Results revealed significant sex differences in the initial baseline functions that were not modifiable by organizational hormones, with males’ duration bisection functions shifted horizontally to the left of females’. Upon the first administration of estradiol, females, but not males, showed a significant, transient leftward shift in their bisection functions, indicative of an increase in clock speed. After extensive retraining in the duration bisection procedure, rats that were exposed to gonadal hormones during the first week of life showed a significant rightward shift in their bisection functions on the fourth day of estradiol administration during each cycle, suggesting a decrease in clock speed. Taken together, our results support the view that there are multiple mechanisms of estrogens’ action in the striatum that modulate dopaminergic activity and are differentially organized by gonadal steroids during early brain development.